Build a super advanced trading bot on DYDX hosted on AWS with Python. (Packt Publishing, 2023)
In this course, you will learn how to develop an end-to-end decentralized trading bot using Python, interact with Telegram for real-time notifications, and leverage the capabilities of AWS to run your code 24/7 in the cloud. The course begins with an introduction to the objectives and expectations, providing a clear roadmap for you. You will explore the concepts of statistical arbitrage and cointegration and understand how to trade the spread based on the Z-score. Dive into the nuances of hedge ratio and half-life and discover how to apply the Kelly Criterion for optimal position sizing and risk management. DYDX FastTrack empowers you to seamlessly configure MetaMask, Alchemy HTTP provider, and access DYDX credentials. Interact with the DYDX API for public price data retrieval and placing orders through the private API. This comprehensive guide includes environment setup in VS Code, Python VENV setup, and creating a collaborative GitHub repository. Master the integration process with environment variables for flawless operations. In the Bot Build stages, you will configure bot constants, construct market prices, and implement cointegration functions. Explore the BotAgent class, which forms the backbone of your trading bot, and effectively manage open trades and exits. Finally, deploy your bot on the AWS cloud, set up real-time Telegram updates, and achieve full automation with CRON. By the end of this course, you will be equipped with the knowledge and skills to develop and deploy an advanced decentralized trading bot on DYDX, leveraging the power of Python and AWS. What You Will Learn Create a statistical arbitrage strategy based on cointegration Implement position sizing and risk management techniques for successful trading Learn how to connect and access DYDX API for trading Understand the concept of z-score and its application in trading spreads Explore Telegram messaging integration for real-time trade notifications Gain proficiency in deploying your bot on AWS for continuous trading Audience This course is ideal for intermediate to advanced Python developers and cryptocurrency enthusiasts aiming to enhance their trading abilities on the DYDX platform. Basic proficiency in Python is required for in-depth coding and bot development. While prior knowledge of cryptocurrency trading strategies is beneficial, it is not mandatory. Access to a computer with internet connectivity is necessary to set up the development environment and interact with DYDX. Familiarity with blockchain technology and decentralized exchanges is recommended for better comprehension. About The Author XCHAIN ANALYTICS LTD: XCHAIN ANALYTICS LTD is a leading analyst and full-stack developer with expertise in Python and React. Their passion lies in discovering and promoting innovative ideas that are often overlooked in the hype-driven tech industry. With a focus on authenticity and practicality, XCHAIN ANALYTICS strives to share their knowledge and empower others through teaching. They believe in the power of continuous learning and experimentation and often find themselves exploring new ventures. However, they always return to teaching as their true calling, where they can put their ideas into action and help others effectively.